2014
DOI: 10.1530/joe-13-0517
|View full text |Cite
|
Sign up to set email alerts
|

Stress in the kidney is the road to pERdition: is endoplasmic reticulum stress a pathogenic mediator of diabetic nephropathy?

Abstract: The endoplasmic reticulum (ER) is an organelle that primarily functions to synthesise new proteins and degrade old proteins. Owing to the continual and variable nature of protein turnover, protein synthesis is inherently an error-prone process and is therefore tightly regulated. Fortunately, if this balance between synthesis and degradation is perturbed, an intrinsic response, the unfolded protein response (UPR) is activated to restore ER homoeostasis through the action of inositol-requiring protein 1, activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 128 publications
(119 reference statements)
0
37
0
1
Order By: Relevance
“…Endoplasmic reticulum (ER) stress is implicated in the pathogenesis of DN [21], and sEH deficiency and pharmacological inhibition attenuate ER stress [22, 23]. Accordingly, the effects of podocyte sEH deficiency on renal ER stress were determined in control and pod-sEHKO mice under normoglycemia and STZ- and HFD-induced hyperglycemia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoplasmic reticulum (ER) stress is implicated in the pathogenesis of DN [21], and sEH deficiency and pharmacological inhibition attenuate ER stress [22, 23]. Accordingly, the effects of podocyte sEH deficiency on renal ER stress were determined in control and pod-sEHKO mice under normoglycemia and STZ- and HFD-induced hyperglycemia.…”
Section: Resultsmentioning
confidence: 99%
“…In line with decreased ER stress, podocyte sEH deficiency attenuated hyperglycemia-induced NF-κB inflammatory response. ER stress is implicated in the pathogenesis of DN [21], and chemical chaperones that mitigate ER stress slow DN progression [46, 47]. Hence, it is reasonable to stipulate that the renal protective effects of podocyte sEH deficiency under hyperglycemia are mediated, at least partly, by decreased ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…13,16,17 Recently, several studies have demonstrated that dysfunction of the ER, or ER stress, is involved in the pathogenesis of diabetes and its complications and the aging process. 14,16,[18][19][20][21][22] Moreover, some reports have suggested the association between ER stress and the vascular function in pathophysiological states. Spitler et al 23 reported that ER stress was increased in the spontaneously hypertensive rat (SHR) aorta, and treatment with chemical chaperones, such as tauroursodeoxycholic acid (TUDCA) and 4-phenylbutyric acid (PBA), ameliorated the increased EDCF-mediated contraction via suppression of the cytosolic phospholipase A 2 (cPLA 2 )/COX pathway.…”
Section: Introductionmentioning
confidence: 99%
“…It plays a principal role in controlling the synthesis, folding and maturation of luminal, secreted and transmembrane proteins (Brandizzi et al 2014;Staehelin 1997;Zhuang and Forbes 2014). During protein synthesis, only those proteins folded in proper configuration and underwent specific post-translational modifications will be processed through the ER secretory pathway and translocated to Golgi bodies (Zhuang and Forbes 2014).…”
Section: Introductionmentioning
confidence: 99%